Rentolog Electric Water Technology - Ojugbani, Onyeka (My University, 2022)
When electricity passes through the system, the electron in the system becomes unstable. sodium ion is highly electronegative. The electron in sodium will pass through aluminium foil but gets trapped in the silicon and elephant grass electrolyte. Grass absorbs photon light from the sun in the process of photosynthesis, but in this way, the grass will store the electrons from electricity as photoelectric also silicon is a good conductor for electricity, therefore electrons can feel comfortable in that region. Similarly, zinc will tend to sacrifice its electron because it is a highly active metal. but it will also be trapped in the electrolyte. Also, fibre grass will block the electron from going out of the system until when it is needed. After it is successfully charged, you can connect your phone, and the electron stored in the electrolyte will charge them.
Keywords: Electricity; Elecric Water technology; Battery